2010
DOI: 10.1507/endocrj.k09e-175
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Thyroid Blocking Antibody (TBAb) on the Thyroid Stimulatory Effect of Human Chorionic Gonadotropin (HCG ) and Equine Chorionic Gonadotropin (ECG)

Abstract: Two kinds of TSH receptor (R) antibody (TRAb) are known. One is the the thyroid stimulating antibody (TSAb) active in hyperthyroidism and other is the thyroid blocking antibody (TBAb) causing primary hypothyroidism. TBAb blocks the thyroid stimulating activity of TSH by the inhibition of TSH binding to the TSHR. TBAb also blocks the thyroid stimulating activity of TSAb by inhibition of TSAb binding to the TSHR [1,2].Human chorionic gonadotropin (HCG) has the thy- . Four thousand iu/mL of HCG and ECG preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Lately, it has been reported that thyroid stimulating type human monoclonal Ab (M22) has similar TSH receptor(R) binding site as TSH; TSHR binding site of H-chain and L-chain of Fab portion of M22 is similar as α-and β-subunit of TSH, respectively [32]. We also reported that TSAb and TBAb have the similar TSH R binding site as α-subunit of TSH [33]. These reports suggest that Fab portion of LATS (TSAb)-IgG is composed of mammalian TSH-like structure except human TSH.…”
mentioning
confidence: 71%
“…Lately, it has been reported that thyroid stimulating type human monoclonal Ab (M22) has similar TSH receptor(R) binding site as TSH; TSHR binding site of H-chain and L-chain of Fab portion of M22 is similar as α-and β-subunit of TSH, respectively [32]. We also reported that TSAb and TBAb have the similar TSH R binding site as α-subunit of TSH [33]. These reports suggest that Fab portion of LATS (TSAb)-IgG is composed of mammalian TSH-like structure except human TSH.…”
mentioning
confidence: 71%
“…In fact, although some weak mAbs created in mice showed weak stimulatory activities to the TSH-R, the TBII activities were also weak [ 24 ]. The TBII activities of human chorionic gonadotropin were weak, as well [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 ) for 1 or 2 hours after the reaction with rhTSH-R. After that, cAMP activities in serum samples S caught up to the level of the control. In contrast, potent blocking serum samples B [ 3 ], or serum samples No. 1 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation